The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12881-019-0908-6
|View full text |Cite
|
Sign up to set email alerts
|

A heterozygous duplication variant of the HOXD13 gene caused synpolydactyly type 1 with variable expressivity in a Chinese family

Abstract: BackgroundSynpolydactyly type 1 (SPD1), also known as syndactyly type II, is an autosomal dominant limb deformity generally results in webbing of 3rd and 4th fingers, duplication of 4th or 5th toes. It is most commonly caused by mutation in HOXD13 gene. In this study, a five-generation Chinese family affected with SPD1 disease were collected. We tried to identify the pathogenic variations associated with SPD1 involved in the family.MethodsWe used the whole genome sequencing (WGS) to identify the pathogenic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previously, Reddy et al, found the p.G91del variant in a large British family with lamellar cataract and demonstrated defective folding and reduced solubility of the mutant protein [ 38 ]. Since then, the p.G91del variant has been reported in 14 families of various ethnicity, mostly causing autosomal dominant congenital nuclear or lamellar cataract, except one with esotropia and nystagmus along with congenital cataract [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Reddy et al, found the p.G91del variant in a large British family with lamellar cataract and demonstrated defective folding and reduced solubility of the mutant protein [ 38 ]. Since then, the p.G91del variant has been reported in 14 families of various ethnicity, mostly causing autosomal dominant congenital nuclear or lamellar cataract, except one with esotropia and nystagmus along with congenital cataract [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both variants had been identified in Danish families by Kjaer et al (2005); the longer duplication explained the polysyndactyly phenotype in a family from Seeland first described in 1932 (Kjaer et al, 2002). Polyalanine expansions in HOXD13 have since been described in Turkish (Tuzel et al, 2007), Pakistani (Wajid et al, 2009), and Chinese (Dai et al, 2005; Gong et al, 2011; Zaib et al, 2019; Zu et al, 2021) kindreds with congenital limb malformations.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous and heterozygous nonsense variants affecting the DNA binding site in the homeodomain of HOXD13 lead to a variety of limb abnormalities and other skeletal defects with reduced penetrance (Jamsheer et al, 2012; Kurban et al, 2011; Low & Newbury‐Ecob, 2012). In addition, variants in the polyalanine tract domains of HOXD13 result in SPD phenotypes (Akarsu et al, 1996; Albrecht et al, 2004; Brison et al, 2012; Gong et al, 2011; Goodman et al, 1997; Kjaer et al, 2005, 2002; Tuzel et al, 2007; Zaib et al, 2019; Zhou et al, 2014). However, alterations outside of these domains can cause a wide spectrum of clinical features making the differential diagnosis complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of genotypic and phenotypic correlations suggested that the longer the polyalanine tract was, the more severe the phenotype was observed ( Goodman et al, 1997 ). Variations of c.183_206dup, c.186_212dup ( Gong et al, 2011 ), and c.893G>A ( Wang et al, 2012 ) in HOXD13 and their co-segregation in affected individuals have been reported by several groups ( Sun et al, 2021 ; Wajid et al, 2009 ; Zaib et al, 2019 ). The variant c.925A>T in HOXD13 causes atypical SPD by impairing the downstream transcription of EPHA7 ( Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%